Estudio de la sostenibilidad empresarial de los servicios bancarios tras el impacto del COVID-19 en entidades financieras ubicadas en San Isidro - Ferrero Barboza, Mateo (2022)
This investigation seeks to find the relationship between Business Sustainability and the Economic Impact on the banking sector of entities linked to the area located in the district of San Isidro. For this purpose, this research considers a literature review for both variables and their evolution in time until now. Likewise, a series of surveys were applied to users of the banking system in the districts of San Isidro, Miraflores, Surco, San Borja and La Molina, where an ad hoc instrument had to be designed, as well as interviews with senior officials of the country's main banking entities, who provided information on the situation of the banking sector in the face of the arrival of COVID-19 in Peru, which we were able to verify with the information received by our respondents, who, for the most part, show their approval of digitization and in turn make use of the new products and services provided by mobile banking to meet their financial obligations more securely and comfortably, highlighting the importance of digitization in banking and the behavior of the pandemic as an accelerator of a new digital consumer profile.